Pemetaan Penelitian Wealth Manajemen (2013 - 2023); dengan Bibliometrik Vosviewer dan Tinjauan Pustaka - Rohmadi; Bagaskara, Doni yusuf; Hikmah, Ulvi Faiqotul (Jurnal Manajemen Indonesia, 2024)
This study aims to map the topic of wealth management using a mix-method approach, which combines biometric studies of VOSviewer and review literature. Research period of 10 years (2013-2023). Data analysis techniques include: (1) mapping the number of journal publications around wealth management; (2) mapping the results of VOSviewer bibilometric visualization related to wealth management topics by mapping network visualization, overley visualization, density visualization; and (3) mapping research topics around wealth management using the Review literature study. The results showed that (1) based on mapping the number of journal publications, there were 300 wealth management topics; (2) Based on network visualization mapping, there are 5 clusters with 65 topics related to wealth management. Based on Overley Visualization mapping, it shows the longest publication year, namely Islamic Wealth Management, and research with the latest year, namely Wealth Management Bank. Based on density visualization mapping, the most researched topics are wealth management, product wealth management and Islamic wealth management while the topics that are rarely studied are bank wealth management, industry, business, accumuation, and firm wealth management, private banking; (3) Based on the mapping of the Review literature, there are 11 topics around wealth management. The application of this research is to map topics related to wealth management and show research rarely researched and popular research to be researched so that it can be a reference for further research with related themes.